Eligibility for clinical trials is unsatisfactory for patients with myelodysplastic syndromes, even at a tertiary referral center. (September 2021) - Nachtkamp, Kathrin; Stark, Josefine; Kündgen, Andrea; Schroeder, Thomas; Strupp, Corinna; Strapatsas, Judith; Schuler, Esther; Kaivers, Jennifer; Giagounidis, Aristoteles; Rautenberg, Christina; Aul, Carlo; Runde, Volker; et al.
Highlights: Inclusion and exclusion criteria of clinical trials are too strict for MDS patients. Rate of inclusion declines over the years 1987−2016. Inclusion rates are lower in pharmaceutically driven trials. MDS patients are a heterogenous group and more comorbid, less rigid criteria needed. Abstract: Participation in clinical trials may allow patients with MDS to gain access to therapies not otherwise available. However, access is limited by strict inclusion and exclusion criteria, reflecting academic or regulatory questions addressed by the respective studies. We performed a simulation in order to estimate the average proportion of MDS patients eligible for participation in a clinical trial. The simulation drew upon 1809 patients in the Düsseldorf MDS Registry whose clinical data allowed eligibility screening for a wide range of clinical trials. This cohort was assumed to be alive and available for study participation. The simulation also posited that all MDS trials (n = 47) conducted in our center between 1987 and 2016 were open for recruitment. In addition, study activities in the year 2016 were analyzed to determine the proportion of patients eligible for at least one of the 9 MDS trials open at that time. On average, each clinical trial was suitable for about 18 % of patients in the simulation cohort. Conversely, 34 % of the patients were eligible for at least one of the 9 clinical studies in 2016. Inclusion/exclusion criteria of studies initiated by the pharmaceutical industry excluded more than twice the fraction of patients compared with investigator initiated trials (potential inclusion of 10 % vs. 21 %, respectively). Karyotype (average exclusion rate 58 %), comorbidities (40 %), and prior therapies (55 %) were the main reasons for exclusion. We suggest that in- and exclusion criteria should be less restrictive, in order to meet the needs of the real-life population of elderly MDS patients.